Використання оборотного перемагнічування у перетворювачах магнітного поля ферозондового типу - Павлик, Любомир Пилипович (Національний університет "Львівська політехніка", 2015)
Дисертацію присвячено вивченню використання оборотного перемагнічування магнітом’яких плівок як осердя перетворювача магнітного поля ферозондового типу на основі збудження магнітним полем, що обертається або здійснює поворотні коливання в площині осердя. Розроблено метод контролю форми поля збудження в перетворювачі на основі перемагнічування обертальним полем. Встановлено, що чутливість до компоненти вимірюваного магнітного поля, перпендикулярної до площини обертання поля збудження, поява паразитної складової сигналу відгуку, пов’язаної з відхиленням площини обертання поля збудження від площини дискового осердя та відхилення її кристалографічної орієнтації, мають однакову природу і виникають лише за умови, що симетрія осей легкого намагнічування осердя відповідає симетрії Sn – дзеркально-поворотна вісь n-ного порядку. Встановлено оптимальні умови для збудження та реєстрації сигналу нелінійного індукційного відгуку ферозондового перетворювача на основі оборотного перемагнічування. Встановлено умови використання двохелементного перетворювача зі збудженням чутливих елементів магнітними полями, що обертаються, для покращення умов виділення інформаційних гармонік та для побудови градієнтометра магнітного поля. Розроблено перетворювач, який живиться від джерела гармонічної напруги. В резонансному режимі збудження залежність його чутливості від частоти поля збудження зростає квадратично. Розроблено перетворювач зі збудженням полем, що здійснює поворотні коливання в площині осердя. Його сигнал відгуку широкосмуговий і це може бути використано для підвищення чутливості перетворювача, якщо застосовувати широкосмугову реєстрацію. Також такий метод збудження дозволяє вимірювати параметри магнітної анізотропії осердя. Диссертация посвящена исследованию использования обратимого перемагничивания магнитомягких пленок в качестве сердечника преобразователя магнитного поля феррозондового типа на основании перемагничивания сердечника магнитным полем, вращающимся в плоскости сердечника. Разработано метод контроля формы поля возбуждения в преобразователе на основании перемагничивания вращающимся полем. Установлено, что чувствительность к компоненте измеряемого поля, перпендикулярной к плоскости вращения поля возбуждения, появление в сигнале отклика паразитной составляющей как следствие отклонения плоскости вращения поля возбуждения от плоскости дискового сердечника а также отклонение его кристаллографической ориентации имеют одну природу и возникают только при условии, что симметрия осей легкого намагничивания соответствует симметрии Sn – зеркально-поворотная ось n-ного порядка. Установлены оптимальные условия для возбуждения и регистрации сигнала нелинейного индукционного отклика феррозондового преобразователя на основании вращательного перемагничивания. Установлены условия для использования двухэлементного преобразователя с возбуждением чувствительных элементов вращающимися магнитными полями для улучшения условий выделения информационных гармоник и для построения градиентометра магнитного поля. Разработано преобразователь с питанием от источника гармонического напряжения. В резонансном режиме возбуждения его чувствительность в зависимости от частоты поля возбуждения растет квадратически. Разработано преобразователь на основании возбуждения полем, выполняющим вращательные колебания в плоскости сердечника. Его сигнал отклика широкополосный и это может быть использовано для улучшения чувствительности прибора при условии использования широкополосной регистрации. Также такой метод возбуждения позволяет измерять параметры магнитной анизотропии сердечника. The thesis is devoted to investigation of the usage of coherent magnetization reversal of the soft magnetic films as a core of the fluxgate-type magnetic field transducer based on magnetization reversal of the core by the field rotating in the core’s plane. The method of controlling the shape of the excitation field of the transducer with magnetization reversal by the rotating filed was developed. Influence of the factors of deviation of the excitation field parameters from the ideal ones affecting the measured signal was estimated: when the amplitudes of the excitation fields provided by the excitation coils differ one from the other by ΔH (elliptical motion of the excitation field vector) and when the plane of rotation of the excitation field deviates from the plane of the core. It was shown that in case of elliptical motion of the excitation field vector some additional components appear in the response signal of the transducer related to this factor. One of them which is directly proportional to ΔH and inversely proportional to the amplitude of the excitation field and appears in the third harmonic of the sensor’s response can be used to adjust the amplitudes of the excitation fields. Another one is the part of the second harmonic of the sensor response. It is proportional to the product of ΔH and the value of the measured signal and inversely proportional to the squared amplitude of the excitation field. That’s why it gives a negligible contribution to the measured signal. When the plane of rotation of the excitation magnetic field deviates from the plane of the core the component that modulates the second harmonic phase appears in the response signal. This component is directly proportional to the product of the tangent of the deviation field angle and the vertical component of the measured field and is inversely proportional to the amplitude of the excitation field. That’s why it also gives insignificant contribution to the measured signal. It was discovered also that sensitivity of such a sensor to the magnetic field component orthogonal to the surface of the rotating excitation field, appearance of the spurious component in the response signal due to declination of the surface of the excitation field rotation from the surface of the core and it’s crystallographic orientation deviation are of the same nature. They appear only on the condition when the symmetry of the axis of easy magnetization of the core corresponds to the symmetry Sn – rotation-reflection axes of the n’s order. Optimal conditions for excitation and registration of the coherent magnetization reversal based fluxgate nonlinear response signal were determined. It was shown that the filling factor of the sensing coil and the saturation magnetization of the material of the core should be as large as possible and the saturation field of the core should be as small as possible. In order to improve the conditions of the informative harmonics extraction as well as for the magnetic field gradiometer construction there were determined conditions of the two-element rotation magnetization reversal transducer usage. The possibility of usage of two such elements situated at a fixed distance one from the other to measure the magnetic field components or it’s gradient depends on the mutual phase of the excitation fields in the coils of transducer, mutual connection of the sensing coils of transducer and the mutual orientation of the sensing elements. Voltage powered mode of magnetic field transducer based on magnetization reversal of the soft magnetic core by rotating magnetic field was investigated. It is shown that when the excitation frequency is twice less than the circuit resonance frequency the fluxgate sensitivity depends on the excitation field frequency quadratically and can exceed the current driven fluxgate sensitivity. At a simultaneous increase of the circuit resonance frequency and the excitation frequency keeping constant their ratio we receive an improved possibility to extract the second harmonics component on the background of the first one. In addition the sensing coil is not needed anymore that simplifies the fluxgate design. The developed model permits to estimate the fluxgate sensitivity and to optimize its design parameters. Taking into account the sensitivity advantages of such a fluxgate at the excitation frequency increase the ferrodielectric materials like the epitaxial iron-garnet films as an active media of such fluxgates should be considered. Transducer based on magnetization reversal of the core by the field performing rotational vibrations in the plane of the core was developed. It has wideband response signal – the effect can be used to improve the sensitivity of the sensor when using the wideband registration method. It was shown also that the ferromodulation effect manifestation in the response signal of such a sensor is connected with magnetic anisotropy of the core when the magnetically anisotropic material is used as sensor core. Experimentally measured angular dependencies of the ferromodulation effect amplitude and their behaviour with a bias field change corresponds well with the model of coherent rotation of the magnetization vector in the uniformly magnetized sample. Ferromodulation response registration can be used for magnetic anisotropy parameters determination and to determine the crystallographic axis directions in the plane of the single crystalline film.
Использование обратимого перемагничивания в преобразователях магнитного поля феррозондового типа
Reversible magnetization reversal usage in the fluxgate-type magnetic field transducers
Keywords: ферозонд; перетворювач магнітного поля; магнітна анізотропія; магнітом’яка плівка; феррозонд; преобразователь магнитного поля; магнитная анизотропия; магнитомягкая пленка; fluxgate; magnetic field transducer; magnetic anisotropy; soft magnetic film